Multi-sensor calibration for an unmanned delivery robot - Xie, Han Seng (Nanyang Technological University, 2024)
The last mile delivery industry is a huge and ever-growing industry with increasing demand for manpower needs. Developments into the use of autonomous mobile robots to address the industry’s manpower demand requirements have been underway. The NTU-Continental Lab have been developing their own autonomous mobile robot named Corriere to facilitate the research and development for this purpose.